2013
DOI: 10.5935/1414-8145.20130019
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral treatment: comprehensive care based on the care model for chronic conditions

Abstract: Objective: To evaluate the adherence to antiretroviral therapy (ART), identifying possible interventions based on the Care Model for Chronic Conditions. Methods: Observational, quantitative, cross-sectional study, involving 215 people with HIV/aids using antiretroviral drugs, between March and June 2012, in Fortaleza, Ceará. From the specific adherence questionnaire, we used nine questions for discussion in the light of the Care Model for Chronic Conditions (MACC). Results: 35.4% failed to adhere to medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
3
8
0
1
Order By: Relevance
“…This is the first study to describe the level of adherence to ART in the municipality of Anápolis, the third largest municipality in the State of Goiás (370,875 inhabitants/2016). Adherence is a major issue in the management of chronic diseases; for people living with HIV/AIDS, the use of ART at prescribed doses and frequencies guarantees great benefits, such as reduction in the occurrence of opportunistic diseases, reduction in the frequency of hospital admissions, reduction in mortality rates, and consequent increase in the time and treatment life quality [19][20][21][22] .Our results indicated that 85% (188/220) of the participants had good or strict adherence to ART and, considering the entire sample, 85% (77/91) of women and 86% (111/129) of men presented good or strict adherence to ART. These results were discordant compared with those of another study that used CEAT-HIV in the State of Ceará, which presented adherence rates of 14% and 48.7% 20 .…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to describe the level of adherence to ART in the municipality of Anápolis, the third largest municipality in the State of Goiás (370,875 inhabitants/2016). Adherence is a major issue in the management of chronic diseases; for people living with HIV/AIDS, the use of ART at prescribed doses and frequencies guarantees great benefits, such as reduction in the occurrence of opportunistic diseases, reduction in the frequency of hospital admissions, reduction in mortality rates, and consequent increase in the time and treatment life quality [19][20][21][22] .Our results indicated that 85% (188/220) of the participants had good or strict adherence to ART and, considering the entire sample, 85% (77/91) of women and 86% (111/129) of men presented good or strict adherence to ART. These results were discordant compared with those of another study that used CEAT-HIV in the State of Ceará, which presented adherence rates of 14% and 48.7% 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations and routines for health services and users are implemented (4) , aiming at obtaining good therapeutic results, resulting in the maintenance of adherence to the treatment and prophylactic measures (5)(6) . Although antiretroviral therapy (ART) enables the increased survival of patients (3) and the prevention of infection in some situations, it does not mean it is easy to be performed (7) . We can consider that the adherence to treatment shows itself as something that is constructed and conquered daily, and its effectiveness occurs when there is clarity of the need of treatment (8)(9) , among other issues.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence is characterized as the establishment of a joint activity, in which the patient is not a mere follower of medical guidance, but understands and agrees with the recommended prescription. In the people living with AIDS, the continued use of antiretroviral medications reduces the level of viral load, improving the immune conditioning, and allowing a better quality of life [3]. However, some factors interfere with medication adherence, by the use of alcohol, drugs, socioeconomic conditions and the non-acceptance of the new health condition.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding such adherence goes through the simple follow-up to the regimen prescribed by health professionals; the identification factors responsible for failures to comply with the treatment are useful, allowing the nurse, as a member of the health team, working more effectively with patients with little adherence and developing strategies to overcome these factors to obtain higher bond rates [2] [3].…”
Section: Introductionmentioning
confidence: 99%